Milkul Yamin dalam Pandangan Syahrur - Widia Ari Susanti; M. Sifa Fauzi Yulianis (Pusat Riset dan Inovasi Nasional, 2025)
Muhammad Syahrur is a contemporary Islamic figure who presents innovative products in interpreting legal verses. One of them is the concept of milkul yamin which allows sexual activities outside of marriage. The focus of the discussion of this paper is to find out how the concept of milkul yamin Muhammad Syahrur, the methodology of Syahrur's legal istinbath, the background of Syahrur's life so that he has a very liberal orientation of thought and how when this milkul yamin concept is applied to Indonesian society. This research is categorized as a literature review (Library Research). Namely research by collecting data on the concept of milkul yamin Muhammad Syahrur to then describe and analyze it simultaneously. The results of this study indicate that Muhammad Syahrur never attended an Islamic school during his life, and when he was studying for his undergraduate, postgraduate, and doctoral degrees, the concentration he took was civil engineering, especially in soil mechanics. On that basis, the methodology of legal istinbath used by Syahrur is the theory of limits (hadd al a'la and hadd al adna), thus giving rise to the concept of milkul yamin which allows sexual intercourse without marriage. While when applied to the lives of Indonesian society, it has many weaknesses both from the legal side and from the socio-cultural side of Indonesian society.